About the role and place of M.V. Pavlov’s scientific heritage in the context of modern biological science development - Deforzh, H. V. (History of science and technology, 2015)
The article highlights the role and place of M.V. Pavlov’s scientific heritage in the context of modern biological science development. It is shown that modern pale zoology (as well as palaeontology in general) is gradually turning into the organisms’ biology of geological past. That is why studies concerning the fossil of vertebrate animals are relevant today. Scientific works of V.О. Kovalevskyi, О.P. Karpinskyi, M.V. Pavlova and L. Dollo proved a great significance of vertebrate animals for the development of major problems in evolutional studies a long ago. The importance of fossils to the stratigraphy and palaeontology is now widely recognized. A big stuff from vertebrates’ pale zoology has been accumulated for nearly 1,5 hundred years. It is used to develop theoretical issues and justification of continental sediments’ stratigraphy in Ukraine.